Hubungan antara Kejadian Computer Vision Syndrome (CVS) dengan Kualitas Tidur Mahasiswa Keperawatan - Dinda Bucira Almaa; Yulia Rizka; Nopriadi, Nopriadi (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Computer Vision Syndrome (CVS) encompasses a constellation of ocular and extraocular symptoms in digital devices users who either habitually or compulsively use digital devices for long periods of time. Digital devices emit blue light (400-490 nm) and generate electromagnetic fields, both of which interfere with the circadian rhythms. This study aims to determine the association between CVS and sleep quality of nursing students. The type of research was observational analytics with a cross-sectional approach and conduct proportionate stratified random sampling. CVS was measured by using CVS-Q, while sleep quality was measured by using PSQI. The analysis used univariate analysis to see the frequency distribution and bivariate used Chi-Square. The result of the data analysis showed that 68,4% of the nursing students experienced CVS. The number of respondents who experienced poor sleep quality was 151 (63.7%). Poor sleep quality was present in 71% of individuals with CVS and 48% of students without CVS. The difference was statistically significant (p=0.001) with OR=2,651. CVS is significantly associated with sleep quality in nurse students. Therefore, it is necessary to apply appropriate behaviors and attitudes to use digital devices and prevent CVS from occurring so that the individual's sleep quality becomes better.